Effect of Communication Management on Distance Learners’ Cognitive Engagement in Malaysian Institutions of Higher Learning - Kayode, Bakare Kazeem (International Review of Research in Open and Distributed Learning, 2018)
Rapid development of communication tools has brought about contentious issues in communication management in distance learning (DL) programs. The aim of this study is to investigate the relationships between communication management indicators, namely, communication practices, communication tools, and students' cognitive engagement in distance learning programs.  A conceptual framework for communication management was developed from Moore’s Transactional Distance Learning Theory (TDLT) and other existing literature. This study was conducted using quantitative research design. A questionnaire (a survey method) was used to elicit responses from 450 randomly selected in-service teachers from three Malaysian Public universities that offer blended mode distance-learning programs. Data analysis was conducted using Analysis of Moment Structures (AMOS) software to test the structural path of communication practices, communication tools, and students' cognitive engagement. Tests of hypotheses provided evidence of measures of fit statistics. The findings provide evidences that effective communication practices and communication tools have strong positive influence on distance students’ cognitive engagement.